Networking and the future of libraries 2 : managing the intellectual record : an international conference held at the University of Bath, 19-21 April 1995 : a festschrift for Philip Bryant - Dempsey, Lorcan; Law, Derek G.; Mowat, Ian R. M.; Bryant, Philip; UK Office for Library and Information Networking (London : Library Association Pub., 1995)
This edited work examines the future and central role of networking for the library and publishing community.
"Published in association with the UK Office for Library and Information Networking, University of Bath."
"Philip Bryant--a bibliography":p. [198]-200.
Includes bibliographical references and index.
hza 29/01/2019
Loans
Keywords: Library information networks; Libraries